“The Ages Humble Servant” : l’écriture de la catastrophe entre modernité et tradition dans The Storm (1704) de Daniel Defoe - Nathalie BERNARD; Emmanuelle PERALDO (E-REA)
Daniel Defoe’s first book-length work, The Storm, was published in 1704, i.e. a few months only after the violent storm that destroyed the southern counties of England and Wales in November 1703. An eye-witness of this disaster, Defoe borrows from records his own experience according to the methods of the New Science and also quotes over sixty letters purportedly written by observers from all over the nation. The writing and composition techniques used in this text led critics to consider The Storm as a pioneering journalistic work. In spite of its immediacy, it claims to be a historical text and a lasting memorial to a disaster that is interpreted as the expression of Providence and God’s “Infinite Power.” We shall see that the tension between novelty and tradition at play in this text makes The Storm a landmark in the development of Defoe’s later fiction writing.